2002
DOI: 10.1037/0022-3514.83.3.711
|View full text |Cite
|
Sign up to set email alerts
|

Self-esteem and persistence in the face of failure.

Abstract: In 2 studies, the authors examined self-esteem, persistence, and rumination in the face of failure. Study 1 manipulated degree of failure and availability of goal alternatives. When an alternative was available, high self-esteem (HSE) participants persisted more than low self-esteem (LSE) participants after a single failure, but less after repeated failure. When no alternative was available, no self-esteem differences in persistence emerged. LSE participants ruminated more than HSE participants. Study 2 examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
129
0
7

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(150 citation statements)
references
References 45 publications
10
129
0
7
Order By: Relevance
“…Regarding the condition of positive feedback, it was argued that feedback would be more attributed to individual achievement and would therefore increase performance. In line with this theory, Di Paula and Campbell (2002) found that participants with high SE persisted more than low SE par-ticipants after a single failure, whereas individuals with low SE ruminated more than high SE individuals. In general, it was expected that high SE individuals would benefit more from positive and negative feedback to improve their performance.…”
Section: Core Self-evaluations and Their Impact On Feedbacksupporting
confidence: 56%
See 1 more Smart Citation
“…Regarding the condition of positive feedback, it was argued that feedback would be more attributed to individual achievement and would therefore increase performance. In line with this theory, Di Paula and Campbell (2002) found that participants with high SE persisted more than low SE par-ticipants after a single failure, whereas individuals with low SE ruminated more than high SE individuals. In general, it was expected that high SE individuals would benefit more from positive and negative feedback to improve their performance.…”
Section: Core Self-evaluations and Their Impact On Feedbacksupporting
confidence: 56%
“…We assume that this could be caused by providing feedback just once between two short tests. In many studies the impact of feedback was examined considering several feedback interventions (e.g., Baron, Ganz, 1972;Di Paula, Campbell, 2002;Heslin, Latham, 2004;. It seems probable that the effect of feedback increases by receiving several feedback interventions, for instance across several feedback loops.…”
Section: Discussionmentioning
confidence: 99%
“…This sense involves positive and negative affects, linking self-esteem conceptually to optimism-pessimism (Smith, Pope, Rhodewalt, & Poulton, 1989). Studies suggest that self-esteem increases motivation , is related to higher overall persistence in targeted goals (Di Paula & Campbell, 2002) and, in adolescents, it is a strong predictor of optimistic or pessimistic orientation in adult life (Heinonen, Raikkonen, & Keltikangas-Jarvinen, 2005). In addition to increasing the probability of success, high self-esteem can also reduce the effect of occasional failure, and thus the risk of developing high levels of pessimism (Campbell, Chew, & Scratchley, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Hal ini dikarenakan mereka percaya bahwa mereka layak mencapai tujuan tertentu karena mereka memiliki harga diri yang lebih tinggi. Kegigihan meningkat karena individu dengan harga diri yang tinggi yakin pada kemampuannya untuk memperoleh hasil tertentu dam memiliki harapan yang besar untuk mencapainya (Di Paula & Campbell, 2002). Penelitian yang dilakukan di Brazil juga menemukan bahwa terdapat korelasi yang positif antara optimisme, harapan dan harga diri (Pacico et al, 2013) hal tersebut sama seperti penelitian yang dilakukan oleh Wong & Lim (2009) yang menemukan bahwa terdapat korelasi positif dengan korelasi antara 0,50 -0,60 antara harapan, optimis dan harga diri.…”
Section: Pendahuluanunclassified